2017
DOI: 10.1016/j.microrel.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of the physical dimensions and material of the semiconductor chip on the reliability of Sn3.5Ag solder interconnect in power electronic module: A finite element analysis perspective

Abstract: This paper primarily focuses on an evaluation study for the temperature cycling capability of tin silver solder interconnect in power electronic applications by the impact of die dimensions and die material properties. The study was investigated on finite element analysis perspective on chip/solder/substrate structure. A commercially available chip was chosen in the finite element analysis (FEA) as the nominal base die. Two thermal cycle profiles were utilised. The effect of die area, die thickness and materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…www.nature.com/scientificreports/ time. Previous studies have reported that the solder joint geometry plays a key role on its useful lifetime 2,42,66 . Principally, the bulkier the solder material, the more elastic and inelastic strains are induced in the solder material leading to accelerated degradation.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports/ time. Previous studies have reported that the solder joint geometry plays a key role on its useful lifetime 2,42,66 . Principally, the bulkier the solder material, the more elastic and inelastic strains are induced in the solder material leading to accelerated degradation.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…( 3 ), one can find that while the contribution of the fatigue failure mechanism in the solder joint degradation heavily depends on the temperature swing ΔT j (temperature heating up and cooling down rates), the contribution of the creep failure mechanism mainly depends on the dwelling temperature and time. Previous studies have reported that the solder joint geometry plays a key role on its useful lifetime 2 , 42 , 66 . Principally, the bulkier the solder material, the more elastic and inelastic strains are induced in the solder material leading to accelerated degradation.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…With the development of the computer, numerical simulation using the finite element analysis (FEA) method is a more appropriate means of pre-analysis than testing. P. Rajaguru and H. Lu et al explored the effect of the geometric parameters of the soldering layer on the ability of solder joints to withstand thermal cycling through the FEA method [5]. They found that the wetting angle and the thickness of the solder layer had positive effects on the solder's ability to withstand thermal cycling, and the angle of inclination had negative effects on the solder layer's ability to withstand thermal cycling.…”
Section: Introductionmentioning
confidence: 99%